Berita Utama Surat Kabar Lokal di Bogor Studi Analisis Isi pada Jurnal Bogor dan Radar Bogor - Maria Fitriah; Fadlya El’Arsya (Jurnal Komunikasi Pembangunan, 2011)
Abstrak Headlines in the newspapers a magnet for readers. Every day people are alyaws served headlines containing about economics, finance, conflicts, politics, law, disaster, and social problems. The headlines should have more value, proximity, conflict and human interest are some of the news value.  The themes and values in the headlines studied using this analysis with a quantitative approach and then know the most dominant themes and news values are most widely used in determining the headlines. The reaserach object is the local daily newspaper in Bogor, Jurnal Bogor and Radar Bogor as a sample. The results showed that most major news theme dominant newspaper in Bogor on Februari 15, 2012 to March 15, 2012 is the theme of news related to disaster and tragedy. Meanwhile, most of the major news theme using actual news the value as the determination of the appropriateness of the news headlines. Keywords: news headlines, themes, news value